L’influence De La Professionnalisation De La GRH Sur La Valorisation Du Métier De L’enseignant- Chercheur : Le Rôle De L’approche Compétence, Cas Des Enseignants Des Grandes Écoles Revue De Littérature Et Essai De Proposition D’un Cadre Conceptuel - Chetouani, Sarah; Balhadj, M. Saïd (European Scientific Journal, ESJ, 2017)
Teaching in universities is currently the main subject of this study, whereby the notions of professionalization and academic pedagogy is considered. The desire to promote the profession of university professor is remarkable as it comes against logics of recognition that are not very compatible. For this reason, particular attention must be paid to the human resource management policy concerning university professors in all aspects of their professional life: their careers, their training needs, their working conditions, and so on. It must also be thought out and focused on results and competitiveness, particularly with regard to the attractiveness and management of positions. This is with a view to ensure better professionalization of the public it trains. The originality of this paper lies in proposing a conceptual framework of reflection and analysis. It aims to understand to what extent the valorization of the profession depends on the professionalization of the HR practices through the setting up of a true competency approach. This approach aims at defining the skills profile of the Moroccan university professors who will serve to better guide and professionalize human resources management activities. Also, the study aims to replace pedagogy as the fundamental competence of the profile of university professor at the heart of the teaching-learning processes of the Moroccan higher education schools.